Loot boxes use, video gaming, and gambling in adolescents: Results from a path analysis before and during COVID-19-pandemic-related lockdown in Italy - Primi, Caterina; Sanson, Francesco; Vecchiato, Marta; Serra, Emilia; Donati, Maria Anna (Frontiers in Psychology, 2022)
Loot Boxes (LBs), i.e., virtual items embedded within video games with numerous features reminiscent of gambling, are increasingly widespread among adolescents. LBs use is associated with problem gambling in youth, but few studies have been conducted on the association between LBs use and gambling behavior considering adolescents. Thus, the mechanisms underlying this relationship are not clear. As LBs use is a significant and positive risk factor for video gaming severity, and video gaming is associated with problem gambling, we hypothesized that LBs use are related to gambling frequency and problem gambling through the intermediary role of video gaming frequency and problem video gaming. We tested our hypothesis before COVID-19-pandemic related lockdown and during COVID-19-pandemic related lockdown, in Italy. . Study 1 was conducted with 1078 high school students (39% boys, mean age = 16.46, SD = 1.28) before COVID-19-pandemic related lockdown, and Study 2 was conducted with 1204 high school students (57% boys, mean age = 15.62, SD = .64) during COVID-19-pandemic related lockdown. A path analysis was carried out to analyze the significance of indirect effects from LBs use to gambling behavior and problem gambling through video gaming and problem video gaming. In both the studies, results showed that LBs use exerted significant and positive direct effects on video gaming frequency, problem video gaming, and gambling frequency. Moreover, LBs use had indirect significant and positive effects on problem gambling through video gaming frequency, problem video gaming, and gambling frequency. Findings attest that LBs use may be related to problem gambling through a greater involvement in videogames. Thus, a specific subtype of young gamblers can develop Gambling Disorder symptoms from the use of LBs and through an intense use of video games. . Practical implications for prevention and treatment are discussed.